ANALISIS YURIDIS PERCOBAAN TINDAK PIDANA PERKOSAAN (STUDI KASUS PUTUSAN NOMOR 87/PID.B/2021/PN.MRH) - Talitha Damayanti; Vience Ratna Multiwijaya (Reformasi Hukum Trisakti, 2022)
Just as the defendant was about to begin his crime, the victim awoke from his nap, shoved the defendant, and yelled, causing the defendant to flee. Are the defendant's activities in compliance with Article 289 of the Criminal Code (Decision No. 87/Pid.B/2021/PN. Mrh) or not? is the first major concern addressed by the author. 2. How is attempted rape punished under Decision Number 87/Pid.B/2021/PN Mrh? This research is descriptive-analytic, and normative legal research. Data gathering makes use of secondary data obtained through literature studies and the data is processed qualitatively using deductive conclusion. The conclusions of this study: in the Judge's Decision Number 87/Pid.B/2021/PN. Mrh, the judge sentenced the defendant with Article 289 of the Criminal Code incorrectly because according to the facts in the trial the defendant fulfilled the elements of Article 53 paragraph (1) in conjunction with Article 285 of the Criminal Code 2) and the defendant was more appropriately charged with Article 285 in conjunction with Article 53 of the Criminal Code, therefore it should be said that an attempted rape with a prison sentence must be reduced by one third of the principal sentence, namely 12 years - 1/3 = 8 years not 7 years.